Protection level of AI H5N1 vaccine clade 2.1.3 commercial against AI H5N1 clade 2.3.2 virus from Ducks to SPF chicken in laboratory conditions - Indriani R; Dharmayanti NLPI (Jurnal Ilmu Ternak dan Veteriner, 2015)
Highly Pathogenic Avian Influenza (HPAI) subtype H5N1 clade 2.3.2 has infected chickens in farms, causing mortality and a decrease in egg production. Vaccination is one of the strategies to control disease of AI subtype H5N1. AI H5N1 clade 2.1.3 vaccine is available commercially. The effectiveness of two vaccines of AI H5N1 clade 2.1.3 (product A and B), and AI H5N1 clade 2.3.2 (Sukoharjo) against AI H5N1 clade 2.3.2 (Sukoharjo) virus SPF chickens was tested in laboratory. Four groups of SPF chickens were used in this study, there were (1) vaccinated with H5N1 clade 2.1.3 (product A), (2) vaccinated with H5N1 clade 2.1.3 (product B), (3) vaccinated with AI H5N1 clade 2.3.2 and (4) unvaccinated (as a control). Each vaccinated group consisted of 10 chicken except 8 chicken for control group. SPF chicken were vaccinated with 1 dose of vaccine at 3 weeks olds, and then after 3 weeks post vaccination (at 6 weeks olds). All group of chicken were challenged with 106 EID50 per 0.1 ml via intranasal. The results showed, chicken vaccinated with H5N1 clade 2.1.3 product A and B gave 100 and 80% protection respectively, but showed challenged virus shedding, whereas vaccine of H5N1 clade 2.3.2 gave 100% protection from mortality and without virus shedding. Vaccines of AI H5N1 clade 2.1.3 product A was better than vaccine product B, and when chicken vaccinated against H5N1 clade 2.3.2, H5N1 clade 2.3.2 vaccine was the best to be used. In order to protect chicken from AI subtype H5N1 clade 2.1.3 and 2.3.2 in the field, a bivalent vaccine of H5N1 clade 2.1.3 and 2.3.2 subtypes should be developed.